2015
DOI: 10.1007/s10096-015-2513-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral moxifloxacin for aerobic vaginitis

Abstract: The purpose of this study was to investigate the therapeutic efficacy of oral moxifloxacin for aerobic vaginitis (AV). We also identified factors that are associated with therapeutic efficacy. This prospective study enrolled general gynecological outpatients at Tianjin Medical University General Hospital between September 2012 and May 2014. Women diagnosed with AV (n = 102) were recruited. All enrolled women were treated with oral moxifloxacin, 400 mg once daily for 6 days (one course). Therapeutic efficacy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[ 91 ] conducted in vitro culture experiments and determined susceptibilities to various antibiotics of 1923 vaginal swabs from AV patients, finding that carbapenems and β-lactam-β-lactamase inhibitor combinations were the most effective antibiotics; moreover, as a category B drug, it could be considered for application to AV patients during pregnancy. Studies have shown that moxifloxacin, a fourth-generation quinolone, shows broad-spectrum antibacterial activity, including against gram-positive bacteria, gram-negative bacteria, anaerobic bacteria and atypical organisms such as mycoplasma, chlamydia and legionella, and shows a significant curative effect on nonpregnant AV patients [ 4 , 92 ]. However, as a category C drug, moxifloxacin can decrease foetal body weight and slightly delay foetal skeletal development, so moxifloxacin should be used during pregnancy only if the potential benefit justifies the potential risk to the foetus.…”
Section: Resultsmentioning
confidence: 99%
“…[ 91 ] conducted in vitro culture experiments and determined susceptibilities to various antibiotics of 1923 vaginal swabs from AV patients, finding that carbapenems and β-lactam-β-lactamase inhibitor combinations were the most effective antibiotics; moreover, as a category B drug, it could be considered for application to AV patients during pregnancy. Studies have shown that moxifloxacin, a fourth-generation quinolone, shows broad-spectrum antibacterial activity, including against gram-positive bacteria, gram-negative bacteria, anaerobic bacteria and atypical organisms such as mycoplasma, chlamydia and legionella, and shows a significant curative effect on nonpregnant AV patients [ 4 , 92 ]. However, as a category C drug, moxifloxacin can decrease foetal body weight and slightly delay foetal skeletal development, so moxifloxacin should be used during pregnancy only if the potential benefit justifies the potential risk to the foetus.…”
Section: Resultsmentioning
confidence: 99%
“…In general authors prefer antimicrobials active against aerobic bacteria such as topical clindamycin,4 kanamycin ovules9 or moxifloxacin 10. Atrophy needs treatment with oestrogen replacement 11.…”
Section: Treatmentmentioning
confidence: 99%
“…The CDC (Centers for Disease Control and Prevention) Sexually Transmitted Infection Treatment Guidelines of 2021 also suggests these treatments (Workowski et al, 2021). For AV, topical vaginal clindamycin or kanamycin or oral other antibacterial drugs that are active against aerobic bacteria such as cefuroxime or moxifloxacin are recommended (Mendling et al, 2016;Wang et al, 2016;Feng et al, 2018). The European (IUSTI/WHO) International Union against sexually transmitted infections (IUSTI) World Health Organisation (WHO) guideline of 2018 also recommends topical clindamycin as the primary treatment for AV (Sherrard et al, 2018).…”
Section: Introductionmentioning
confidence: 99%